The Effect of Work-Life Balance and Spirituality on Ethical Behaviour of the Workplace - Novera Kartikawati Sudiro; Zaenal Fanani (Jurnal Reviu Akuntansi dan Keuangan, 2020)
This research aimed to obtain information and empirical evidence on work-life balance and spirituality to ethical behaviour. This research was conducted at the Public Accountant in East Java. This research uses primary data to obtain vital information from respondents using the saturated sampling method. Respondents of this study were 102 auditors who work at the Public Accountant in East Java. This study uses a causality analysis Structural Equation Model (SEM) based component or variance or with the model name of Partial Least Square (PLS). Hypothesis testing will be done with the help of software Warp PLS 5.0. This research indicates that work-life balance is proved to have a significant positive effect on auditor ethical behaviour, and spirituality has a significant negative effect on ethical behaviour. The research's main objectives are to test the relationship of work-life balance and spirituality to find out whether they contribute to auditors' ethical behaviour.